Sustainability Reporting and Firm Perfomance Based On Maqashid Sharia Perspective - Meydinda Usman, Reza; Restuningdiah, Nurika; Juliardi, Dodik (International Journal of Science, Technology & Management, 2025)
This study aims to determine the effect of disclosure of sustainability reporting on company performance based on maqashid sharia perspective in sharia stock indexed companies in Indonesia. The study obtained a sample of 52 companies in the mining, property & real estate, energy, and basic industry & chemicals sectors listed in the Indonesian Sharia Stock Index (ISSI) during 2022-2023, resulting in 104 observations through purposive sampling. The data analysis technique was conducted using documentation methods, specifically by collecting annual report data and sustainability reports from the sample companies. The analysis was performed using multiple regression with E-Views 13 software. Based on the research results, the Sustainability Reporting does not have a statistically significant effect on the Maqashid Syariah Index. This research indicates that companies listed in the Indonesian Sharia Stock Index, although they have demonstrated concern for environmental issues and social interests through sustainability reporting, have not yet fully integrated the principles of Maqashid Sharia into their operational practices in an optimal manner.